Research progress on the role and mechanism of DNA damage repair in germ cell development - Wang, Yan; Su, Mengrong; Chen, Yujie; Huang, Xinyu; Ruan, Lian; Lv, Qizhuang; Li, Li (Frontiers in Endocrinology, 2023)
In the complex and dynamic processes of replication, transcription, and translation of DNA molecules, a large number of replication errors or damage can occur which lead to obstacles in the development process of germ cells and result in a decreased reproductive rate. DNA damage repair has attracted widespread attention due to its important role in the maintenance and regulation of germ cells. This study reports on a systematic review of the role and mechanism of DNA damage repair in germline development. First, the causes, detection methods, and repair methods of DNA damage, and the mechanism of DNA damage repair are summarised. Second, a summary of the causes of abnormal DNA damage repair in germ cells is introduced along with common examples, and the relevant effects of germ cell damage. Third, we introduce the application of drugs related to DNA damage repair in the treatment of reproductive diseases and related surgical treatment of abnormal DNA damage, and summarise various applications of DNA damage repair in germ cells. Finally, a summary and discussion is given of the current deficiencies in DNA damage repair during germ cell development and future research development. The purpose of this paper is to provide researchers engaged in relevant fields with a further systematic understanding of the relevant applications of DNA damage repair in germ cells and to gain inspiration from it to provide new research ideas for related fields.